An active reactive bid-based market model using fuzzy sets - M. H. Gomes (2008)
The restructuring of power systems has often originated the organization of power system operation planning in a set of chronological sequence of activities that are reasonably decoupled. This means that the Market Operator purely economic schedule together with bilateral contracts is conveyed to the System Operator to be validated from a technical point of view. The System Operator also has to schedule reactive power but some of its reactive power requirements may be unfeasible given the previous active power schedules and the alternator capability diagram. Apart from this aspect, active and reactive powers are coupled in determining the eventual violation of branch thermal limits and reactive power has a well-known local nature. While recognizing the Coupling between active and reactive powers, the models presented in this paper admit that the Market Operator schedule may have to be altered either because there are branch limit or nodal voltage violations or because the System Operator requires a reactive output that can not be provided Clue to the previous active schedule. The changes on the initial schedule are determined by solving an optimization problem that uses adjustment generator or demand bids. Apart from that, we adopted a symmetric fuzzy programming approach recognizing that some constraints have a soft nature, namely the ones related with voltage and branch flow limits. To solve the resulting non-linear problem we used Sequential Linear Programming, SLP. At its final iteration this problem also Outputs active and reactive nodal marginal prices useful to build more effective tariff systems. The paper includes a case study based on the IEEE 24 bus test system.